Innovations in Indian healthcare: Unlocking the benefits of telehealth and telemedicine - Parekh, Zainab; Suryawanshi, Yogesh (Science Center Group, 2025)
Telehealth and telemedicine enable virtual consultations between healthcare providers and patients through video calls, telephone, and online platforms, improving access to healthcare services, particularly for populations in remote areas. These technologies help overcome geographical barriers and enhance healthcare delivery efficiency. This review examines the development, applications, challenges, and future opportunities of telehealth and telemedicine in India, including issues related to technological infrastructure, digital literacy, and regulatory frameworks. It also highlights the potential of emerging technologies such as artificial intelligence, remote monitoring, and data analytics to strengthen telehealth services, reduce healthcare disparities, and improve health outcomes.